Basalt fiber composite board and preparation method thereof
By crushing, melting, braiding and activate the basalt fiber web, combined with the thermoset polyimide layer, the problem of strength reduction caused by damage to the fiber is solved, and the adhesion and strength of the basalt fiber composite panel is improved.
Patent Information
- Application Number
- CN202411308398.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
The strength reduction problem caused by fiber damage during the preparation process of basalt fiber composite plates. Existing methods such as acid-base etching or plasma modification method can damage the fibers and affect the performance of the composite plates.
Granules are made by crushing basalt, melted into spinning solution, brushed into fibers, braided into fiber webs, and soaked and baked through γ-aminopropyltriethoxysilane-ethanol solution and silica as activator. The dry fiber web forms an activated fiber web and is heat-pressed to form a composite board with a thermoset polyimide layer.
It improves the adhesion between fibers and other materials, enhances the strength of the composite plate, and the activator used does not contain strong acids or alkalis, and will not damage the surface of the fibers, forming fine protrusions to improve adhesion.
Smart Images

Figure CN119283395A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fiber composite board, and in particular to a basalt fiber composite board and a preparation method thereof. Background Art
[0002] Basalt fiber has the characteristics of high strength and good high temperature stability, and is widely used in composite materials. However, due to the smoothness of basalt fiber, the bonding force between basalt fiber and other materials is weak, which will reduce the performance of basalt fiber composite board.
[0003] In order to improve the adhesion between basalt fiber and other materials, acid-base etching or plasma modification is generally used to roughen the surface of basalt fiber. However, both methods will damage the surface of basalt fiber, affecting the strength of basalt fiber and further affecting the strength of basalt fiber composite board. There are also some other methods to improve the adhesion of basalt fiber surface, but they are only in the early test stage and are not suitable for industrial production. Summary of the invention
[0004] The main purpose of the present invention is to provide a basalt fiber composite board and a preparation method thereof, which solves the technical problem that the strength of the existing basalt composite board is reduced due to damage to the basalt fibers during the preparation process.
[0005] In order to achieve the above object, the present invention provides a method for preparing a basalt fiber composite board, comprising the following steps:
[0006] S1, crushing basalt to obtain basalt particles, melting the basalt particles to obtain a spinning solution, and drawing the spinning solution to obtain basalt fibers;
[0007] S2, weaving a plurality of the basalt fibers to obtain a coarse basalt fiber, and weaving a plurality of the coarse basalt fibers to obtain a basalt fiber mesh;
[0008] S3, activating the basalt fiber mesh to obtain an activated basalt fiber mesh;
[0009] S4, laying multiple layers of thermosetting polyimide and multiple layers of the activated basalt fiber mesh in the mold from bottom to top to obtain a mixed material;
[0010] S5. Hot-pressing the mixed material to obtain a basalt fiber composite board.
[0011] Preferably, in step S1, the melting temperature of the basalt particles is 1400-1500° C., and the diameter of the basalt fibers is 15-25 μm.
[0012] Preferably, in step S2, the linear density of the coarse basalt fiber is 2500-3500 tex.
[0013] Preferably, the method for preparing the activated basalt fiber mesh in step S3 comprises the following steps:
[0014] A. dissolving γ-aminopropyltriethoxysilane in an ethanol solution to obtain a γ-aminopropyltriethoxysilane-ethanol solution, and adding silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution to obtain an activator;
[0015] B. soaking the basalt fiber mesh in the activator;
[0016] C. After soaking, the mixture is dried to obtain an activated basalt fiber mesh.
[0017] Preferably, the mesh spacing of the activated basalt fiber mesh is 0.5-1 mm.
[0018] Preferably, in step A, the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8):3;
[0019] In the γ-aminopropyltriethoxysilane-ethanol solution, the content of γ-aminopropyltriethoxysilane is 1-2wt%;
[0020] The weight ratio of the silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution is (3-4):100.
[0021] Preferably, in step B, the weight ratio of the basalt fiber mesh to the volume ratio of the activator is (40-50):1;
[0022] The ratio of weight to volume is g:L.
[0023] Preferably, in step S4, the thickness of a single layer of the thermosetting polyimide is 0.3-0.6 mm, the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide, and the top layer and the bottom layer of the mixed material are both thermosetting polyimide layers.
[0024] Preferably, in step S5, the hot pressing temperature is 180-220° C., the pressure is 15-18 MPa, and the holding time is 30-40 min.
[0025] The invention also discloses a basalt fiber composite board made by the above method.
[0026] The beneficial effects achieved by the present invention are:
[0027] The activated basalt fiber mesh of the present invention can enhance the bonding force, thereby improving the strength of the basalt fiber composite board;
[0028] The present invention uses γ-aminopropyltriethoxysilane-ethanol solution and manganese dioxide as activators, does not contain strong acid or strong alkali, and will not damage the surface of basalt fiber. The activator in the present invention can interact with the surface of basalt fiber to form fine protrusions on the surface of basalt fiber, thereby increasing the roughness of the surface of basalt fiber, enhancing the bonding force between basalt fiber and other materials, and improving the strength of basalt composite board. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0030] Figure 1 It is a schematic diagram of a basalt fiber composite board disclosed in a specific embodiment of the present invention.
[0031] Description of reference numerals:
[0032] 1. Thermosetting polyimide layer; 2. Activated basalt fiber mesh layer. DETAILED DESCRIPTION
[0033] The technical scheme in the embodiment of the present invention is described clearly and completely below in conjunction with the accompanying drawings in the embodiment of the present invention. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0034] The present invention discloses a method for preparing a basalt fiber composite board, comprising the following steps:
[0035] S1. Crush basalt into basalt particles. The particle size of the basalt particles can be determined according to actual production needs. Generally, the particle size of the basalt particles is about 40 μm. Melt the basalt particles at 1400-1500° C. to obtain a spinning solution. Use a drawing furnace to make the spinning solution into basalt fibers. The diameter of the basalt fibers is 15-25 μm.
[0036] S2. Using a stranding machine to make a plurality of basalt fibers into one strand, a coarse basalt fiber is obtained. The number of basalt fibers can be selected according to actual conditions. The linear density of the obtained coarse basalt fibers is between 2500 and 3500 tex. The coarse basalt fibers are woven into a basalt fiber mesh. The mesh spacing of the basalt fiber mesh is 0.5 to 1 mm.
[0037] S3, activating the basalt fiber mesh, preparing the activated basalt fiber mesh, the activated basalt fiber mesh can be better bonded with the composite material, the production steps of the activated basalt fiber mesh are:
[0038] A. Dissolving γ-aminopropyltriethoxysilane (hereinafter referred to as KH550) in an ethanol solution to obtain a KH550-ethanol solution, and then adding silicon dioxide to obtain an activator;
[0039] The volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8):3;
[0040] In the KH550-ethanol solution, the content of KH550 is 1-2wt%;
[0041] The weight ratio of silicon dioxide to KH550-ethanol solution is (3-4):100.
[0042] B. Soak the basalt fiber mesh in the activator, the weight of the basalt fiber mesh and the volume ratio of the activator is (40-50):1;
[0043] Among them, the ratio of weight to volume is g:L.
[0044] C. After soaking for 3 hours, the fiber was dried at 70°C to obtain an activated basalt fiber mesh.
[0045] S4. Lay multiple layers of thermosetting polyimide and multiple layers of activated basalt fiber mesh in the mold from bottom to top to obtain a mixed material, wherein the thermosetting polyimide and the activated basalt fiber mesh are laid alternately, the top layer and the bottom layer of the mixed material are both thermosetting polyimide layers, and the thickness of a single layer of thermosetting polyimide is 0.3 to 0.6 mm.
[0046] S5. Hot-pressing the mixed material to obtain a basalt fiber composite board, wherein the hot-pressing temperature is 180-220° C., the pressure is 15-18 MPa, and the holding time is 30-40 min.
[0047] like Figure 1 As shown, the present invention also discloses a basalt fiber composite board, comprising a thermosetting polyimide layer 1 and an activated basalt fiber mesh layer 2, wherein the top and bottom layers of the composite board are both thermosetting polyimide layers 1, and activated basalt fiber mesh layers 2 are bonded between the thermosetting polyimide layers 1.
[0048] Example 1 A method for preparing a basalt fiber composite board
[0049] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0050] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0051] S3, activating the basalt fiber mesh, the specific steps are:
[0052] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0053] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 40g:1L;
[0054] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0055] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.4 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0056] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0057] Example 2 A method for preparing a basalt fiber composite board
[0058] S1. Crush basalt into 40 μm basalt particles, melt them at 1500° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0059] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 3500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0060] S3, activating the basalt fiber mesh, the specific steps are:
[0061] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 8L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 4g:100g, to prepare an activator;
[0062] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 40g:1L;
[0063] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0064] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.6 mm, the number of activated basalt fiber mesh layers is 3, and a mixed material is obtained.
[0065] S5. Maintain the mixed material at 220° C. and 15 MPa for 40 minutes to obtain a basalt fiber composite board.
[0066] Example 3 A method for preparing a basalt fiber composite board
[0067] S1. Crush basalt into 40 μm basalt particles, melt at 1450° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers is 25 μm.
[0068] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 3000tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 1mm.
[0069] S3, activating the basalt fiber mesh, the specific steps are:
[0070] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7.5L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 2wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3.5g:100g, to prepare an activator;
[0071] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 50g:1L;
[0072] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0073] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.5 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0074] S5. Maintain the mixed material at 220° C. and 16 MPa for 40 minutes to obtain a basalt fiber composite board.
[0075] Example 4: A method for preparing a basalt fiber composite board
[0076] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 20 μm.
[0077] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.7mm.
[0078] S3, activating the basalt fiber mesh, the specific steps are:
[0079] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1.5wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0080] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 45g:1L;
[0081] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0082] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.4 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0083] S5. Maintain the mixed material at 200° C. and 18 MPa for 35 minutes to obtain a basalt fiber composite board.
[0084] Example 5
[0085] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0086] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0087] S3, activating the basalt fiber mesh, the specific steps are:
[0088] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0089] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 40g:1L;
[0090] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0091] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.3 mm, the number of activated basalt fiber mesh layers is 3, and a mixed material is obtained.
[0092] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0093] Comparative Example 1
[0094] S1. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0095] S2, soaking 5mm short chopped basalt fiber in activator, the weight of short chopped basalt fiber and the volume ratio of activator is 40g:1L;
[0096] S3, after fully soaking for 3 hours, drying at 70°C to obtain activated chopped basalt fibers;
[0097] S4. Lay thermosetting polyimide and activated short chopped basalt fibers in the mold from bottom to top. Lay thermosetting polyimide and short chopped basalt fibers alternately. The bottom layer and the top layer are both thermosetting polyimide layers. The thickness of the thermosetting polyimide layer is 0.4 mm. The number of layers of activated short chopped basalt fibers is 3 to obtain a mixed material.
[0098] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0099] Comparative Example 2
[0100] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0101] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0102] S3, activating the basalt fiber mesh, the specific steps are:
[0103] A. Add an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%;
[0104] B. Soak the basalt fiber mesh in KH550-ethanol solution, and the volume ratio of the basalt fiber mesh to the activator is 40g:1L;
[0105] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0106] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.4 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0107] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0108] Comparative Example 3
[0109] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0110] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0111] S3, activating the basalt fiber mesh, the specific steps are:
[0112] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 1g:100g, to prepare an activator;
[0113] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 40g:1L;
[0114] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0115] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.4 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0116] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0117] Comparative Example 4
[0118] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0119] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0120] S3, activating the basalt fiber mesh, the specific steps are:
[0121] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0122] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 60g:1L;
[0123] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0124] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.4 mm, the number of layers of the activated basalt fiber mesh is 3, and a mixed material is obtained.
[0125] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0126] Comparative Example 5
[0127] S1. Crush basalt into 40 μm basalt particles, melt them at 1400° C. to obtain a spinning solution, and use a drawing instrument to make the spinning solution into basalt fibers, the diameter of the basalt fibers being 15 μm.
[0128] S2. Using a stranding machine to make a strand of coarse basalt fiber from the basalt fiber, the linear density of the coarse basalt fiber is 2500tex, and then weaving the coarse basalt fiber into a basalt fiber mesh, the mesh spacing of the basalt fiber mesh is 0.5mm.
[0129] S3, activating the basalt fiber mesh, the specific steps are:
[0130] A. Adding an appropriate amount of KH550 to an ethanol solution (the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is 7L:3L) to prepare a KH550-ethanol solution, wherein the content of KH550 is 1wt%; adding silicon dioxide to the KH550-ethanol solution, the weight ratio of silicon dioxide to KH550-ethanol is 3g:100g, to prepare an activator;
[0131] B. Soak the basalt fiber mesh in the activator, and the weight of the basalt fiber mesh and the volume ratio of the activator are 40g:1L;
[0132] C. After fully soaking for 3 hours, dry at 70°C to obtain the activated basalt fiber mesh.
[0133] S4. Lay thermosetting polyimide and activated basalt fiber mesh in the mold from bottom to top, alternately lay the thermosetting polyimide and activated basalt fiber mesh, the bottom layer and the top layer are both thermosetting polyimide layers, the thickness of the thermosetting polyimide layer is 0.7 mm, the number of activated basalt fiber mesh layers is 3, and a mixed material is obtained.
[0134] S5. Maintain the mixed material at 180° C. and 15 MPa for 30 minutes to obtain a basalt fiber composite board.
[0135] Bending strength test
[0136] The basalt fiber composite boards prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to a tensile test machine to measure the bending strength of the composite boards according to GB / T1449-2005. Each group of composite boards was measured 5 times and the average value was recorded. The measurement results are shown in Table 1.
[0137] Table 1
[0138]
[0139]
[0140] It can be seen from Table 1 that the basalt composite board prepared according to the method of the embodiment has good flexural strength at room temperature and low temperature. Referring to Example 1 and Comparative Example 1, it can be seen that after the basalt fiber mesh is replaced by short chopped basalt fibers, the flexural strength of the composite board is reduced. Therefore, the use of basalt fiber mesh can effectively improve the flexural strength of the composite board. Referring to Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that adding manganese dioxide to the KH550 ethanol solution can effectively improve the flexural strength of the composite board. It may be that manganese dioxide is attached to the surface of the basalt fiber mesh. surface, increasing the roughness of the basalt fiber mesh surface, and increasing the bonding force between the basalt fiber mesh and the thermosetting polyimide; referring to Example 1 and Comparative Example 4, it can be seen that adding too much basalt fiber mesh to the activator will reduce the activation quality, thereby reducing the bonding force between the basalt fiber mesh and the thermosetting polyimide, affecting the flexural strength of the composite board; referring to Example 1 and Comparative Example 5, it can be seen that when the thermosetting polyimide layer is too thick, the flexural strength of the composite board is reduced, which may be related to the fact that the basalt fiber mesh skeleton cannot support thermosetting polyimide of this thickness.
[0141] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a basalt fiber composite board, characterized in that: The following steps are involved: S1, crushing basalt to obtain basalt particles, melting the basalt particles to obtain a spinning solution, and drawing the spinning solution to obtain basalt fibers; S2, weaving a plurality of the basalt fibers to obtain a coarse basalt fiber, and weaving a plurality of the coarse basalt fibers to obtain a basalt fiber mesh; S3, activating the basalt fiber mesh to obtain an activated basalt fiber mesh; S4, laying multiple layers of thermosetting polyimide and multiple layers of the activated basalt fiber mesh in the mold from bottom to top to obtain a mixed material; S5. Hot-pressing the mixed material to obtain a basalt fiber composite board.
2. The method for preparing a basalt fiber composite board according to claim 1, characterized in that: In step S1, the melting temperature of the basalt particles is 1400-1500° C., and the diameter of the basalt fibers is 15-25 μm.
3. The method for preparing a basalt fiber composite board according to claim 1, characterized in that: In step S2, the linear density of the coarse basalt fiber is 2500-3500 tex.
4. The method for preparing a basalt fiber composite board according to claim 1, characterized in that: The method for preparing the activated basalt fiber mesh in step S3 comprises the following steps: A. dissolving γ-aminopropyltriethoxysilane in an ethanol solution to obtain a γ-aminopropyltriethoxysilane-ethanol solution, and adding silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution to obtain an activator; B. soaking the basalt fiber mesh in the activator; C. After soaking, the mixture is dried to obtain an activated basalt fiber mesh.
5. The method for preparing a basalt fiber composite board according to claim 4, characterized in that: The mesh spacing of the activated basalt fiber mesh is 0.5-1 mm.
6. The method for preparing a basalt fiber composite board according to claim 4, characterized in that: In step A, the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8):3; In the γ-aminopropyltriethoxysilane-ethanol solution, the content of γ-aminopropyltriethoxysilane is 1-2wt%; The weight ratio of the silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution is (3-4):
100.
7. The method for preparing a basalt fiber composite board according to claim 4, characterized in that: In step B, the weight ratio of the basalt fiber mesh to the volume ratio of the activator is (40-50):1; The ratio of weight to volume is g:L.
8. The method for preparing a basalt fiber composite board according to claim 1, characterized in that: In step S4, the thickness of the single layer of the thermosetting polyimide is 0.3-0.6 mm, the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide, and the top layer and the bottom layer of the mixed material are both thermosetting polyimide layers.
9. The method for preparing a basalt fiber composite board according to claim 1, characterized in that: In step S5, the hot pressing temperature is 180-220° C., the pressure is 15-18 MPa, and the holding time is 30-40 min.
10. A basalt fiber composite board, characterized in that: The basalt fiber composite board is made by the preparation method of any one of claims 1 to 9.